International Graduate Students: Social Networks and Language Use - Moglen, Daniel (Journal of International Students, 2017)
The campus climate for international graduate students (IGSs) has been gaining attention in recent years as the number of IGSs in the United States continues to rise. IGSs bring diversity to the campus community and enrich the academic community, but also come to the table with distinct needs, concerns, and experiences. The current study is primarily concerned with how early social and academic experiences affect English learning and academic success. Social networks outside of the student’s cultural background may be difficult to develop, and, therefore, it is not uncommon to see students gravitate towards others who share their cultural and language background.